2022
DOI: 10.3390/nu14142969
|View full text |Cite
|
Sign up to set email alerts
|

Honeys as Possible Sources of Cholinesterase Inhibitors

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disease characterised by low levels of the neurotransmitter (acetylcholine), oxidative stress, and inflammation of the central nervous system. The only currently available form of treatment entails the administration of AChE/BChE (acetylcholinesterase/butyrylcholinesterase) inhibitors to patients diagnosed with the disease. However, AD prevention is possible by administering the correct inhibitors with food. The aim of this study was to examine 19 typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Such positive effects were attributed by the authors to the presence of polyphenols. More recently, Szwajgier et al 37 evidenced the potential benefits of nineteen types of honey, which can represent an important font of cholinesterase inhibitors, playing a role in the Alzheimer disease. Honey also inhibits the growth of pathogens, which presence and diffusion can damage the Central Nervous System.…”
Section: Resultsmentioning
confidence: 99%
“…Such positive effects were attributed by the authors to the presence of polyphenols. More recently, Szwajgier et al 37 evidenced the potential benefits of nineteen types of honey, which can represent an important font of cholinesterase inhibitors, playing a role in the Alzheimer disease. Honey also inhibits the growth of pathogens, which presence and diffusion can damage the Central Nervous System.…”
Section: Resultsmentioning
confidence: 99%
“…Only six in vitro articles were found related to the search topic. Of the six in vitro honey studies, two in vitro articles [ 29 , 30 ] investigated AD and PD, whereas three in vitro articles [ 31 , 32 , 33 ] specifically targeted AD only. One in vitro study [ 34 ] investigated the relationship between honey and neurodegeneration.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of BChE has been reported to treat advanced AD [ 45 ]. A recent study assessed nineteen honey varieties’ inhibitory activity on AChE and BChE using Ellman’s colorimetric approach [ 33 ]. Thyme and Goldenrod honey significantly inhibit AChE and BChE with the highest degree of inhibition of 21.17% and 34%, respectively, raising the prospect that honey may be utilized as a future AD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[60] There are limited studies on the evaluation of the acetylcholinesterase (AChE) and tyrosinase inhibition activities of SH. Szwajgier et al [61] reported the AChE inhibition activity range between 14 % and 16 % and BChE inhibitory activity between 18 % and 20 % in Ukraine SH. The anti-tyrosinase activity of two SHs from different regions of Thailand was found as 46.64 % and 52.12 %.…”
Section: Anticholinesterase Anti-urease Anti-tyrosinase and Antiinfla...mentioning
confidence: 99%